Pengaruh Likuiditas, Ukuran Perusahaan, dan Leverage Terhadap Kebijakan Dividen Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Pada Tahun 2019-2021 - Lia, Anggi; Hidayat, Taufik (Asosiasi Dosen Akuntansi Indonesia, 2024)
The aim of the research is to examine the influence of liquidity, company size and leverage on dividend policy in manufacturing companies listed on the Indonesian Stock Exchange in 2019-2021. The sampling method used was a purposive sampling method, so that 129 sample companies were obtained times 3 years of observation with 387 observations. Research data was obtained from audited financial reports or annual reports, sample data was taken from the website www.idx.co.id. The data analysis technique used is descriptive statistics and Logistic Regression Analysis with the SPSS 23 test tool. The partial test results show that the liquidity variable has a significant effect on dividend policy. The variable company size in a partial test has a significant effect on dividend policy. The leverage variable in a partial test has a significant effect on dividend policy